The Effect of Equal Channel Angular Pressing (ECAP) on the Microstructure and Hardness of A356 Aluminium Alloy - Ishak, N. N. M.; Salleh, M. S.; Yahaya, S. H.; Mohamad, E.; Sulaiman, M. A. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Equal channel angular pressing (ECAP) is one of popular techniques of severe plastic deformation (SPD), a process of producing an ultra-fine grained (UFG) microstructure. This work focused on the microstructural analysis and mechanical properties of A356 aluminium alloy after processing by ECAP. Cooling slope casting and conventional casting techniques were used to produce feed materials for ECAP process. ECAP process was carried out at room temperature by route A for one pass. The microstructure observation was carried out before and after ECAP under optical microscope as well as its hardness. It is found that the microstructure distribution of ECAPed sample in combination with cooling slope casting was more homogeneous compared to the microstructure of ECAPed sample in combination with as-cast. The results also showed an obvious reduction of grain size after the alloy was pressed using ECAP process with average grain size of 58μm for cooling slope ECAPed and 96μm for as-cast ECAPed. The hardness of the alloy increased after ECAP process with an increment about 33.6% for conventional casting and 21.2% increment for cooling slope casting sample.